Defective Gating and Proteostasis of Human ClC-1 Chloride Channel: Molecular Pathophysiology of Myotonia Congenita - Jeng, Chung-Jiuan; Fu, Ssu-Ju; You, Chia-Ying; Peng, Yi-Jheng; Hsiao, Cheng-Tsung; Chen, Tsung-Yu; Tang, Chih-Yung (Frontiers in Neurology, 2020)
The voltage-dependent ClC-1 chloride channel, whose open probability increases with membrane potential depolarization, belongs to the superfamily of CLC channels/transporters. ClC-1 is almost exclusively expressed in skeletal muscles and is essential for stabilizing the excitability of muscle membranes. Elucidation of the molecular structures of human ClC-1 and several ClC homologues provides important insight to the gating and ion permeation mechanisms of this chloride channel. Mutations in the human CLCN1 gene, which encodes the ClC-1 channel, are associated with a hereditary skeletal muscle disease, myotonia congenita. Most disease-causing CLCN1 mutations lead to loss-of-function phenotypes in the ClC-1 channel and thus increase membrane excitability in skeletal muscles, consequently manifesting as delayed relaxations following voluntary muscle contractions in myotonic subjects. The inheritance pattern of myotonia congenita can be autosomal dominant (Thomsen type) or recessive (Becker type). To date over 200 myotonia-associated ClC-1 mutations have been identified, which are scattered throughout the entire protein sequence. The dominant inheritance pattern of some myotonia mutations may be explained by a dominant-negative effect on ClC-1 channel gating. For many other myotonia mutations, however, no clear relationship can be established between the inheritance pattern and the location of the mutation in the ClC-1 protein. Emerging evidence indicates that the effects of some mutations may entail impaired ClC-1 protein homeostasis (proteostasis). Proteostasis of membrane proteins comprises of biogenesis at the endoplasmic reticulum (ER), trafficking to the surface membrane, and protein turn-over at the plasma membrane. Maintenance of proteostasis requires the coordination of a wide variety of different molecular chaperones and protein quality control factors. A number of regulatory molecules have recently been shown to contribute to post-translational modifications of ClC-1 and play critical roles in the ER quality control, membrane trafficking, and peripheral quality control of this chloride channel. Further illumination of the mechanisms of ClC-1 proteostasis network will enhance our understanding of the molecular pathophysiology of myotonia congenita, and may also bring to light novel therapeutic targets for skeletal muscle dysfunction caused by myotonia and other pathological conditions.